Ageing Without Care? The Healthcare Insecurity Among the Elderly in Nigeria - Oluwakemi (Magyar Gerontológia, 2025)
This paper provides a review of studies of the healthcare insecurity experienced by the elderly population in Nigeria, focusing on social isolation, economic struggle, inadequate healthcare, and the potential lack of governmental support.